MANAJEMEN PERENCANAAN PEMBANGUNAN PERUMAHAN PADA DINAS PERUMAHAN PERMUKIMAN DAN PERTANAHAN KABUPATEN BULUKUMBA (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study purposed to find out how the Management of Housing Development Planning at the Department of Housing, Settlements and Land in order to realize livable housing. This study used descriptive qualitative research.  The number of informants in this study was 10 (ten) people. By using data collection techniques, namely interviews, documentation, media review and direct observation. The results of the study showed that the Management of Housing Development Planning at the Department of Housing, Settlements and Land had been running optimally. This seen based on the 3 (three) indicators used, namely: Planning, Implementation, Evaluation and control. From planning was optimal, it could be seen in the tasks and functions to achieve the level of effectiveness and operational efficiency. In terms of implementation, it was good because we could see from all the plans that had prepared, it run well and was implemented properly. Finally, in terms of evaluation and control, it were optimal, because it had been known what strategies or plans need to be added or reduced, what tools or facilities need to be prepared to carry out the program, how long additional time was needed, and so on.